The role of the digitized milk collection point in increasing milk quality and income of smallholder dairy farmers in Pangalengan-Bandung - Erwidodo Erwidodo; Tri Bastuti Purwantini; Iwan Setiajie Anugrah; Ening Ariningsih; Handewi Purwati Saliem; Erma Suryani (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
The low quality of fresh milk has become one of the main constraints smallholder dairy farmers face in almost all developing countries, including Indonesia. The low quality of fresh milk has resulted in lower prices received by farmers. It can even result in the rejection of milk by milk processors, which is detrimental to smallholder farmers. This paper aims to analyze the impact of automated and digitized milk collection points (AD-MCPs) on the quality of fresh milk, the price of milk, and smallholder dairy farmers' income in Pangalengan, Bandung, West Java. The data and information of 300 households are part of the baseline survey of 600 smallholder dairy farmers in four districts of West Java between July and September 2017. The results show that AD-MCP facilities have successfully encouraged smallholder dairy farmers to adopt and implement improved management practices to increase dairy cows' productivity and fresh milk quality, resulting in increased prices and farm income. Therefore, the government needs to endorse, facilitate, and accelerate the development of AD-MCPs to increase domestic fresh milk production, quality of fresh milk, and dairy farmers' income. AD-MCP development is implemented through a partnership between dairy farmers, cooperatives, and milk processors.